2007
DOI: 10.1073/pnas.0701428104
|View full text |Cite
|
Sign up to set email alerts
|

Exploring lignification in conifers by silencing hydroxycinnamoyl-CoA:shikimate hydroxycinnamoyltransferase in Pinus radiata

Abstract: The enzyme hydroxycinnamoyl-CoA:shikimate hydroxycinnamoyltransferase (HCT) is involved in the production of methoxylated monolignols that are precursors to guaiacyl and syringyl lignin in angiosperm species. We identified and cloned a putative HCT gene from Pinus radiata, a coniferous gymnosperm that does not produce syringyl lignin. This gene was up-regulated during tracheary element (TE) formation in P. radiata cell cultures and showed 72.6% identity to the amino acid sequence of the Nicotiana tabacum HCT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 30 publications
4
144
1
2
Order By: Relevance
“…Furthermore, p-hydroxyphenylglycerol end units were observed in a dehydrogenation polymer (that was never subjected to ball milling) obtained using p-coumaryl alcohol as monomer . Finally, arylglycerol end units were shown to be increased in lignins rich in p-hydroxyphenyl units and in lignins that were obtained by down-regulating p-coumarate 3-hydroxylase in alfalfa (Medicago sativa; Ralph et al, 2006) or hydroxycinnamoyl-CoA:shikimate hydroxycinnamoyltransferase in Pinus radiata lignifying cell cultures (Wagner et al, 2007). These results indicate that arylglycerol end units are a feature of natural lignins, as suggested previously (Higuchi et al, 1974).…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, p-hydroxyphenylglycerol end units were observed in a dehydrogenation polymer (that was never subjected to ball milling) obtained using p-coumaryl alcohol as monomer . Finally, arylglycerol end units were shown to be increased in lignins rich in p-hydroxyphenyl units and in lignins that were obtained by down-regulating p-coumarate 3-hydroxylase in alfalfa (Medicago sativa; Ralph et al, 2006) or hydroxycinnamoyl-CoA:shikimate hydroxycinnamoyltransferase in Pinus radiata lignifying cell cultures (Wagner et al, 2007). These results indicate that arylglycerol end units are a feature of natural lignins, as suggested previously (Higuchi et al, 1974).…”
Section: Discussionsupporting
confidence: 76%
“…RNAi has recently been established for white spruce (A. Séguin, unpublished data) and has not yet been reported to be successful in any other conifer except for radiata pine (Pinus radiata; Wagner et al, 2007Wagner et al, , 2009). Since Sitka spruce and white spruce are closely related species (Yeh and Arnott, 1986), we used white spruce as a suitable system for analysis of the effect of targeted RNAi on CYP720B transcript levels and diterpenoid metabolites.…”
Section: Cyp720b4 Rna Interference Causes Changes In Dra Compositionmentioning
confidence: 99%
“…These include: a thioglycolic acid lignin assay (Möller et al 2003); Klason lignin analysis (Möller et al 2005b); thioacidolysis (Möller et al 2005a(Möller et al , 2005bWagner et al 2013); two dimensional nuclear magnetic resonance (Wagner et al 2007); an acetyl bromide lignin assay (Wagner et al 2007); alkalinenitrobenzene oxidation (Sato et al 2011); pyrolysis-gas chromatography coupled mass spectroscopy (Pillai et al 2011); and Fourier-transform infrared (FTIR) spectroscopy (Pillai et al 2011). In some cases, similar methods are applicable to the analysis of cell-wall polysaccharides, e.g.…”
Section: Biochemical Analysis Of Tracheary Elementsmentioning
confidence: 99%
“…Möller et al (2005b) reported the silencing of cinnamyl alcohol dehydrogenase, an enzyme associated with the formation of cell wall polymers such as lignin, using RNA interference. Suppression of genes associated with the monolignol pathway in pine, such as 4CL and HCT (encoding 4-coumarate CoA ligase and p-hydroxycinnamoyl-CoA shikimate hydroxycinnamoyltransferase), resulted in substantial lignin reductions of up to 50-60% (Wagner et al 2007;Wagner et al 2009). Suppression of a putative Pinus radiata clone (PrCCoAOMT) encoding the lignin-related enzyme caffeoyl CoA 3-O-methyltransferase (CCoAOMT) caused a reduction in lignin content of 5-20% in Pinus radiata TE cultures.…”
Section: Molecular Analysis Of Tracheary Elementsmentioning
confidence: 99%
See 1 more Smart Citation